Prospective study of food intake changes in adolescent elite athletes - Maria Larsson; Ida Lindman; Josefin Abrahamson; Agneta Hörnell (BMJ Nutrition, Prevention & Health)
Background Inadequate energy intake among athletes can lead to low energy availability (LEA) which in turn can result in negative effects on athletic performance and physical and psychological health. This syndrome is known as relative energy deficiency in sports (REDs).Objective To map perceived changes in overall food intake among adolescent athletes during the previous year, as well as weekly changes during a 3-month period and to examine how these changes are associated with mental health, physical load and sex.Methods A total of 168 high school athletes from eight different sports participated. A baseline questionnaire examined changes in training habits and food intake in the past year, mental health (short version of the Warwick-Edinburgh Mental Well-being Scale (SWEMWBS)), injury history and previous periods of poor psychological health. Weekly digital questionnaires for 3 months tracked weekly physical and mental load and changes in food intake. Comparative and correlation analyses were performed with p<0.05 considered significant.Results A decreased food intake during the previous year was reported more often among athletes experiencing periods of poor mental health than those without such periods (10% vs 2%; p=0.034). Athletes who decreased their food intake reported lower mental well-being than athletes who increased their food intake (mean difference in SWEMWBS=4.69±1.57; p=0.021). Over a 3-month period, most athletes did not change their food intake, yet fluctuations in physical load were reported.Conclusion This study showed that athletes experiencing lower mental health or period(s) of poor mental health reported decreased food intake more often than those with better mental health or those without period(s) of poor mental health. In addition, the mismatch found between perceived weekly changes in overall food intake and changes in physical load during the same time period could potentially result in an increased risk for LEA.